The knowledge of Nursing Academics about Death and the Process of Dying (Revista Iberoamericana de Bioética, 2024)
Death is the gradual and systemic loss of vital functions responsible for survival. In this sense, this study aimed to reveal the construction of nursing students’ knowledge of death and the dying process. This is a descriptive and qualitative study, carried out with 37 students in the last year of nursing at a public university in Brazil. The data was used to create the textual corpus for Reinert's Analysis in IRaMuTeQ software. Four categories emerged: 1) the importance of pain relief for the dignity of the patient and family; 2) nursing support in assisting family members at the time of death; 3) the feeling of impotence in the face of the patient's death and dying process; and 4) the need to work on death and the dying process during their studies. There was a gap in the education system regarding topics such as the process of finitude.
Keywords: nursing students; death; nursing care; hospice and palliative care nursing